Arsenic Exposure to Fish and Shellfish Consumption among Community in Makassar, Indonesia - Musfirah Musfirah; Sri Damayanty (International Journal of Public Health Science (IJPHS), 2016)
Fish and shellfish contaminated by Arsenic (As) heavy metals from people activity discharge into the coast. Coastal community was exposure risk by As due to consumption of marine products. This study aimed to determine of  human health risks level who consume fish and shellfish that contain As in Kaluku Bodoa and Untia coastal, Makassar. This research designed by observational and Environmental Health Risk Analysis (EHRA) approach. Human sample were 49 people and 8 environmental samples that selected based on certain criteria. Data collected through environmental assestment, interview and anthropometric data measurement. Data analyzed with EHRA methods. The results showed that the highest mean As levels found in Leiognatus equulus fish i.e. 1.589 mg/kg and Gafrarium tumidum shellfish i.e. 4.244 mg/kg of Untia coastal. The mean level of the carcinogenic risk for fish and shellfish consumption were unacceptable  because they  contain  As that demonstrated value of more than exponent 4 (ECR > E-4) and non-carcinogenic risk mean level was value of more than 1 (RQ > 1). Fish and shellfish consumption considered unsafe and will impact health problems for the community. Community should be restrict the frequency and amount of fish and shellfish consumption.